Modularity in Health and Social Services: Perspectives on Organization and Management - Vähätalo, Mervi (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Organizations that provide health and social services operate in a complex and constantly changing environment. Changes occur, for example, in ageing, technology and biotechnology, and customers’ expectations, as well as the global economic situation. Organizations typically aim to adapt the changes by introducing new organizational structures and managerial practices, such as process and lean management. Only recently has there been an interest in evaluating whether organizations providing health and social services could apply modularity in order to respond to some of the changes. The concept of modularity originates from manufacturing, but is applied in many other disciplines, such as information technology and logistics. However, thus far, the literature concerning modularity in health and social services is scarce. Therefore the purpose of this thesis is to increase understanding concerning modularity and the possibilities to apply modularity in the health and social services context. In addition, the purpose is to shed light on the viewpoints that are worth taking into account when considering the application of modularity in the health and social services context. The aim of the thesis is to analyze the way in which the modular structures are applied in the health and social services context and to analyze what advantages and possible barriers, as well as managerial concerns, might occur if modularity is applied in the health and social services context. The thesis is conducted by using multiple methods in order to provide a broad aspect to the topic. A systematic literature review provided solid ground for pre-understanding the topic and supported the formulation of the research questions. Theoretical reasoning provided a general overview of the special characteristics of the health and social services context and their effect on application of modularity. Empirical studies concentrated on managerial concerns of modularity particularly from the perspective of health and social services for the elderly. Results of the thesis reveal that structures in products, services, processes, and organizations are rather modular in health and social services. They can be decomposed in small independent units, while the challenges seem to occur especially in the compatibility of the services. It seems that health and social services managers have recognized this problem and they are increasingly paying attention to this challenge in order to enhance the flexible compatibility of services. Advantages and possible barriers of modularity are explored in this thesis, and from the theoretical perspective it could be argued that modularity seems to be beneficial in the context of health and social services. In fact, it has the potential to alleviate several of the challenges that the health and social services context is confronting. For example, modular structures could support organizations in their challenging task to respond to customers’ increasing demand for heterogeneous services. However, special characteristics of the health and social services context create barriers and provide significant challenges in application of modularity. For example, asymmetry of information, negative externalities, uncertainty of demand, and rigid regulation prevent managers from extensively drawing benefits from modularity. Results also reveal that modularity has managerial implications in health and social service. Modularity has the potential to promote and support new service development and outsourcing. Results also provide insights into network management and increases managerial understanding of different network management strategies. Standardization in health and social services is extensive due to legislation and recommendations. Modularity provides alternative paths to take an advantage of standardization while still ensuring the quality of the services. Based on this thesis, it can be concluded, both from a theoretical perspective and from empirical results concerning modularity in health and social services, that modularity might fit well and be beneficial. However, the special characteristics of the health and social services context prevent some of the benefits of modularity and complicate its application. This thesis contributes to the academic literature on the organization and management of health and social services by describing modularity as an alternative way for organizing and managing health and social services. In addition, it contributes to the literature of modularity by exploring the applicability of modularity in the context of health and social services. It also provides practical contribution to health and social services managers by evaluating the pros and cons of modularity when applied to health and social services.

Modulaarisuus sosiaali- ja terveydenhuollossa: Näkökulmia organisointiin ja johtamiseen Sosiaali- ja terveyspalveluita tuottavien organisaatioiden toimintaympäristö on kompleksinen ja alati muuttuva. Toimintaympäristön muutokset liittyvät muun muassa väestön ikääntymiseen, teknologisiin ja bioteknologisiin muutoksiin, asiakkaiden muuttuviin odotuksiin sekä maailman kokonaistaloudellisen tilanteen muutoksiin. Organisaatioilla on taipumusta sopeutua muutoksiin ottamalla käyttöön uusia organisointimalleja ja johtamistapoja, kuten esimerkiksi prosessijohtaminen tai lean-johtaminen. Viimeaikoina on herännyt kiinnostus arvioida, voisivatko sosiaali- ja terveydenhuollon organisaatiot hyödyntää modulaarisuutta toimintaympäristön muutoksiin sopeutumisessa. Modulaarisuus käsitteenä on peräisin valmistavasta teollisuudesta, mutta sitä on sovellettu myös muilla aloilla, muun muassa tietotekniikassa ja logistiikassa. Modulaarisuuden hyödyntämisestä sosiaali- ja terveydenhuoltoon on toistaiseksi vain vähän tietoa. Tämän tutkimuksen tavoitteena onkin lisätä ymmärrystä modulaarisuudesta ja mahdollisuuksista soveltaa modulaarisuutta sosiaali- ja terveydenhuoltoon. Lisäksi tavoitteena on tuoda esille näkökulmia, joiden huomioon ottaminen on tärkeää pohdittaessa modulaarisuuden käyttöönottoa sosiaali- ja terveydenhuollossa. Tutkimuksen tarkoituksena on analysoida, miten modulaariset rakenteet näyttäytyvät sosiaali- ja terveydenhuollossa. Lisäksi tarkoituksena on analysoida, mitä etuja modulaarisuudella voidaan saavuttaa ja mitä mahdollisia esteitä sen käyttöönotolle voi olla. Lisäksi tarkastellaan, mitä johtamiseen liittyviä näkökulmia modulaarisuuden soveltamisessa tulisi huomioida. Näkökulmien monipuolisuuden turvaamiseksi, tutkimuksessa hyödynnettiin useita erilaisia tutkimusmenetelmiä. Perehtyminen aiheeseen systemaattisen kirjallisuuskatsauksen avulla auttoi muodostamaan esiymmärryksen aiheesta ja tarkentamaan tutkimuskysymyksiä. Teoreettisen päättelyn avulla tarkasteltiin sosiaali- ja terveydenhuollon erityispiirteitä ja niiden vaikutuksia modulaarisuuden sovellettavuuteen. Empiirisissä tutkimuksissa tarkasteltiin modulaarisuutta johtamisen, erityisesti vanhuspalveluiden johtamisen, näkökulmasta. Tutkimuksen tulosten perusteella voidaan todeta, että tuotteiden, palveluiden, prosessien ja organisaatioiden rakenteet ovat varsin modulaarisia sosiaali- ja terveydenhuollossa. Rakenteiden pilkkominen pienempiin osakokonaisuuksiin on jokseenkin yksinkertaista. Sen sijaan haasteita ilmenee erityisesti osien yhteenliitettävyydessä. Sosiaali- ja terveydenhuollon johtajat ovat kuitenkin tunnistaneet ongelman ja kiinnittävät asiaan enenevässä määrin huomiota mahdollistaakseen osakokonaisuuksien joustavan yhdistelyn. Teoreettisen tarkastelun perusteella voidaan todeta, että sosiaali- ja terveydenhuolto voi hyötyä modulaarisuuden soveltamisesta. Modulaarisuus voi auttaa kohtaamaan joitakin sosiaali- ja terveydenhuoltoon kohdistuvista haasteista, esimerkiksi asiakkaiden heterogeenisiin tarpeisiin vastaamista voidaan tukea modulaaristen rakenteiden avulla. Sosiaali- ja terveydenhuollon erityispiirteet voivat kuitenkin aiheuttaa esteitä tai ainakin merkittäviä haasteita modulaarisuuden soveltamiselle. Esimerkiksi, tiedon epäsuhta, negatiiviset ulkoisvaikutukset ja alan voimakas sääntely heikentävät modulaarisuudesta saatavia hyötyjä. Tutkimuksen tulokset paljastivat myös modulaarisuuden vaikutuksia sosiaali- ja terveydenhuollon johtamiseen. Modulaarisuus voi edistää uusien palveluiden kehittämistä ja tukea tuotteiden ja palveluiden alihankintaa. Tulokset avaavat uusia näkökulmia verkostojohtamiseen ja edistävät erilaisten verkostojohtamis-strategioiden ymmärtämistä. Rakenteiden näkeminen modulaarisena auttaa hahmottamaan, miltä osin tuotteiden ja palveluiden standardointi edistää vaikuttavuutta ja innovaatioita. Tämän tutkimuksen perusteella voidaan sekä teoreettisesti että empiirisesti tarkasteltuna todeta, että modulaarisuus soveltuu sosiaali- ja terveydenhuoltoon melko hyvin. Sosiaali- ja terveydenhuollon erityispiirteet heikentävät osittain modulaarisuudesta saatavia hyötyjä ja hankaloittavat modulaarisuuden käyttöön-ottoa. Tutkimus edistää teoreettista ymmärrystä sosiaali- ja terveydenhuollon organisoinnista ja johtamisesta kuvaamalla modulaarisuutta yhtenä vaihtoehtoisena organisointitapana ja siihen liittyviä johtamisen näkökulmia. Lisäksi tutkimus syventää modulaarisuuteen liittyvää kirjallisuutta kuvaamalla, miten modulaarisuutta voidaan hyödyntää juuri tässä kontekstissa. Tutkimus kuvaa myös modulaarisuutta sosiaali- ja terveydenhuollossa käytännön hyödyntämisen näkökulmasta ja tuo esille niitä etuja ja haittoja, joita modulaarisuuden soveltamisesta voi aiheutua.